PENYULUHAN TENTANG KESEHATAN GIGI DAN MULUT DENGAN MENGGUNAKAN ALAT PERAGA DAN TANPA ALAT PERAGA TERHADAP TINGKAT PENGETAHUAN SISWA/I KELAS V SD NEGERI 107955 LUBUK PAKAM KAB. DELI SERDANG - Yetti Lusiani; Netty Jojor Aritonang; Aminah br Saragih (Poltekkes Kemenkes Medan, 2023)
Maintaining oral and dental health is definitely one effort to improve health. One of the reason some people keep ignoring oral and dental health problem is lack of knowledge and awareness the importance of dental and oral health. Therefore, it is necessary to give education about it. This study was conducted for 5th grade students in 107955 Lubuk Pakam, Deli Serdang Regency. Total samples are 40 students. The result of this study showed that there were 20 students’ knowledge level was good (100%) after given education with models, however there were 16 students’ knowledge level was good (80%) and 4 students’ knowledge was average (20%). Therefore, it is known that education with models can improve students’ knowledge level so that it’s understandable rather than without models.